HEPATOPROTECTIVE ACTIVITY OF LINK LIVECARE IN CARBON TETRACHLORIDE AND D-GALACTOSAMINE INDUCED HEPATOTOXICITY IN ICR MICE - Karunarathna, A.U.; Chandrika, U.; Padumadasa, C.; Seneviratne, B.; Abeysekera, A.M. (Moksha Publishing House, 2017)
Attached

TIlt: liver is the most important organ concerned with metabolic activities in the human body. The human body is constantlv bombarded with xenobiotics in the form of drugs and environmental toxins which can damage the liver. There is much current interest in herbal formulations claiming to be hepatoprotectivc agents. The hepatoprotectivc activity of an isopropanol.water (70:30 vI\') extract of the proprietary mixture of the 14 plants, flndrogrophis paniculala. Eclipla alba. Phyllanrhus nmnrus, Phylianrhus emblica , Terminalia chebula, Terminalia belie,;ca, Tinospom (·ooifolia, Curcuma longa, Glycyrrhiza glabra, Boerrhavia diffusa.Osbekia octandm. Tephrosia purpurea, Piper long"'" and ·Vemollia cinerea, used in the preparation ofthe Ayurvedic formulation, LINK LIVECARE™ was studied against carbon tetrachloride (0.08 ml/kg) and galactosamine (800 mg!kg) intoxication in ICR male mice. The animals were pretreated for seven days prior to intoxication. Both biochemical and histopathological changes of the liver were investigated. Significant (p < 0.05) hepatoprotective effects were observed for the extract tested at doses ranging from 40 rug/kg to 280 rag/kg. It showed optimum protection at the dose of 80 rug/kg against carbon tetrachloride induced hepatotoxicity lowering the increase of AST, ALT, ALP and TB by 46,46,83 and 64% respectively, compared with silymarin at a dose of 50 mglkg which lowered the increase of the same parameters by 60,67,80 and 89% respectively. The extract also significantly lowered the increase of AST, ALP and TB when the toxicant was galactosamineH. OlI'el'eT, there was no effect on .11 T levels. Pretreatment reduced the extent ofliva necrosis caused by both toxicants.
Keywords: LINK LlVECARE, poly herbal formulation, hepatoprotection, carbon tetrachloride, galactosamine